Efficient yellow phosphorescent [3+2+1] Ir (Ⅲ) complex for warm white lighting and visible light communication. (January 2022) - Li, Wansi; Wang, Zhaoming; Zhang, Meng; He, Miao; Zhang, Si-Wei; Yang, Chen; Wu, Yuan; Li, Jingzhou; Tang, Man-Chung; Fu, Hongyan; Wei, Guodan
Abstract: An efficient yellow-emitting iridium (Ⅲ) phosphorescent material named Ir-Lpt-CN has been strategically designed as a color converter in solid-state white light-emitting diodes (WLEDs) for naturally warm white light and visible light communication (VLC). This complex with a [3 + 2+1] configuration has a high photoluminescent quantum efficiency of 77%. When blending with silicone at 5 wt.%, the gallium nitride-based WLED achieves a luminous efficiency of 90 lm/W, an excellent color rendering index of 66.8, a correlated color temperature of 3, 959 K, and Commission Internationale de L'Eclairage (International Commission on Illumination) coordinates of (0.37, 0.32), approximately the standard white light. Through optimizing the bias current of the WLED and delivering the 4-quadrature amplitude modulation data stream, a VLC system with 50 cm free space has been established to achieve data rates 34.2 Mbps below a forward error correction criterion of 3.8 × 10 −3 . At a voltage of 3.2 V, this thermally stable material successfully reaches a −3 dB bandwidth of 26.3 MHz, illustrating the highly stable bandwidth performance of these WLEDs. This material instigates further development in the field of white light VLC and warm white light illumination. Graphical abstract: Image 1 Highlights: A novel yellow Ir-Lpt-CN phosphorescent material has high photoluminescent quantum yield. It has been designed as a stable and efficient color converter in solid-state white light-emitting diodes (WLEDs). The WLEDs have demonstrated naturally warm white light and visible light communication. The WLEDs have approximately the standard warm white light feature. The data setup system with WLEDs has shown a highly stable bandwidth performance.